Аналіз коливань відповідальних елементів енергоблоку потужністю 200 МВт при кінематичних навантаженнях - Гонтаровський, Павло Петрович; Гармаш, Наталія Григорівна; Глядя, Алла Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Забезпечення надійності енергетичного обладнання на всіх режимах роботи є важливим і актуальним завданням. Визначені характеристики вібронавантаженості відповідальних елементів енергоблоку потужністю 200 МВт при перехідних коливальних процесах, викликаних сейсмічним навантаженням. Для дослідження коливань використовуються розроблені розрахункова методика й програмне забезпечення. Отримані результати показали, що переміщення роторів відносно корпусів циліндрів, верхньої фундаментної плити відносно нижньої в розглянутому випадку не перевищують допустимих значень. Результати проведених досліджень можуть бути використані при оцінці сейсмостійкості турбоагрегатів різної потужності.

An important problem that should be resolved during the power plant operation is related to the reliability control for all modes of operation including extreme external dynamic effects of a natural character, in particular the earthquakes. The vibrations of the elements of power equipment exposed to seismic forces occur due to kinematic perturbations that are transmitted from the ground to the bottom base plate. In this connection, the following requirements are set up to the seismic stability of the power equipment of power plants that include its strength, impermeability and its serviceability when exposed to seismic forces. The loading of the fasteners of the turbine generating unit of 200MW arranged on the base was analyzed in the case of exposure to seismic forces. Calculation methods and the software were used that were developed using the finite element method. The computational model of the dynamic system, in particular the turbine generating unitbed and base consisted of arbitrary-oriented rods and lumped masses that are rigidly interconnected with each other or these can also be interconnected by linear and nonlinear elastically-damped elements. The rod finite elements with distributed parameters allow us to take into consideration all the types of deformations that occur during rod vibrations. The computational method allows us to take into consideration the structural peculiarities of the system and the peculiarities of its behavior during possible earthquakes. The kinematic perturbation that simulates the seismic action transmitted from the ground to the bottom bed plate is assigned by the accelerogram that includes acceleration in three mutually perpendicular directions. The computations were done for the synthesized seismogram of the earthquake of wind force 7 that results in the broadest spectrum of the loading in comparison with other real seismograms. The analysis of the computational data obtained for the seismic stability of the turbine generating unit of 200MW showed that the displacement of rotors towards the turbine generating unit axis relatively the cylinder bodies and the displacement of the upper bed plate relatively the bottom bed plate is lower than permissible values in the case of the earthquake of wind force 7.The keyed joints are the most loaded system assemblies though the strains that arise in them during the kinematic perturbations in question also fail to attain permissible values. The obtained research data are of practical importance and can be used for the assessment of the seismic stability of turbine generating units of a different power.
Analyzing the vibrations of the critical components in the power generating unit of 200MW under kinematic loadings
Keywords: сейсмічне навантаження; пружно-демпферні елементи; seismic load; elastically-damped elements